Systematics of the genus Soesilarishius (Araneae: Salticidae: Euophryinae) - Ruiz, Gustavo Rodrigo Sanches (Zootaxa, 2011)
The genus Soesilarishius Makhan, 2007 is revised: a diagnosis and a redescription are proposed based on the type species, seven new species from northeastern Brazil and Soesilarishius aurifrons (Taczanowski, 1878) comb. nov. from Peru. The previously monotypic genus contains now 9 species and is characterized by the reduced spiraled embolus. The species S. minimus sp. nov., S. lunatus sp. nov., S. cymbialis sp. nov. and S. dromedarius sp. nov. are described based on specimens from the State of Pernambuco, while S. crispiventer sp. nov., S. spinipes sp. nov. and S. albipes sp. nov. are based on specimens from the State of Bahia. In addition, the type series of Euophrys aurifrons Taczanowski, 1878 from Peru is revised, a lectotype is designated and the male palp is illustrated for the first time.